2017
DOI: 10.3389/fnbeh.2017.00151
|View full text |Cite
|
Sign up to set email alerts
|

Persistent Decreases in Adult Subventricular and Hippocampal Neurogenesis Following Adolescent Intermittent Ethanol Exposure

Abstract: Neurogenesis in hippocampal dentate gyrus (DG) and subventricular zone (SVZ) matures during adolescence to adult levels. Binge drinking is prevalent in adolescent humans, and could alter brain neurogenesis and maturation in a manner that persists into adulthood. To determine the impact of adolescent binge drinking on adult neurogenesis, Wistar rats received adolescent intermittent ethanol (AIE) exposure (5.0 g/kg/day, i.g., 2 days on/2 days off from postnatal day, P25–P54) and sacrificed on P57 or P95. Neural … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(40 citation statements)
references
References 62 publications
(99 reference statements)
1
37
2
Order By: Relevance
“…We found that binge alcohol alone elicited a bilateral proliferative response in the SVZ, as alcohol only treated animals exhibited up to a fourfold increase in BrdU + cells at 24 hr compared to controls, similar to the magnitude observed after TBI alone. This is in contrast with previous studies using different alcohol intoxication models in rodents which reported that alcohol caused significant depression in SVZ and subgranular zone (SGZ) proliferation as examined at various time points (5 hr up to 41 days) post alcohol exposure (Anderson, Nokia, Govindaraju, & Shors, ; Liu & Crews, ; Nixon & Crews, ). However, one report found that discontinuing chronic alcohol administration led to an increase in SGZ cell number at day 2 and 7 after cessation (Anderson et al, ).…”
Section: Discussioncontrasting
confidence: 84%
“…We found that binge alcohol alone elicited a bilateral proliferative response in the SVZ, as alcohol only treated animals exhibited up to a fourfold increase in BrdU + cells at 24 hr compared to controls, similar to the magnitude observed after TBI alone. This is in contrast with previous studies using different alcohol intoxication models in rodents which reported that alcohol caused significant depression in SVZ and subgranular zone (SGZ) proliferation as examined at various time points (5 hr up to 41 days) post alcohol exposure (Anderson, Nokia, Govindaraju, & Shors, ; Liu & Crews, ; Nixon & Crews, ). However, one report found that discontinuing chronic alcohol administration led to an increase in SGZ cell number at day 2 and 7 after cessation (Anderson et al, ).…”
Section: Discussioncontrasting
confidence: 84%
“…Humans with AUD suffer from global subtle neurodegeneration and reduced hippocampal volumes associated with deficits in cognition and increased negative affect [4,5]. Preclinical studies in rats find alcohol exposure decrease hippocampal dentate gyrus (DG) neurogenesis [6] and increase markers of DG-induced neuronal death including: classic H&E, TUNEL, silver stain, Fluoro Jade B staining, and electron microscopyidentified necrotic morphology as well as immunohistochemistry (IHC) for active (cleaved) caspase-3+IR (CC3+IR) [7][8][9][10]. Alcohol exposure also increases brain neuroimmune gene expression, which mimics that found in postmortem human AUD brain and is hypothesized to contribute to alcohol-induced neurodegeneration [3,11] and the development of AUD [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…during adolescence producing average peak blood ethanol concentrations (BECs) in the range of 130–200 mg/dL (see Kim et al, in press), similar to those estimated for binge drinking in early adolescents (Donovan, 2009). Adolescent exposure to ethanol in this range in rats has been shown to induce long-lasting behavioral and neural alterations that are not evident in controls receiving water i.g (Broadwater & Spear, 2014; Liu & Crews, 2017; Vetreno et al, 2017; Risher et al, 2015a,b; Swartzwelder et al, 2017). For instance, we have shown long-lasting and sex-dependent detrimental consequences of repeated intermittent i.g.…”
Section: Introductionmentioning
confidence: 99%